Reflecting and learning: A grounded theory on reframing deficit views of young indigenous women and safety. Issue 6 (2nd June 2020) - Wilson, Denise; Cootes, Karina; Mikahere-Hall, Alayne; Sherwood, Juanita; Berryman, Kay; Jackson, Debra
Abstract: Often young indigenous women are framed in ways that problematize and pathologize them, which overlooks their strengths. We interviewed 16 young Indigenous Māori women aged 14 to 18 years about their understandings of safety, being safe, and how they kept themselves and their friends safe. Reflecting and Learning, aided by progressing age and maturity, is the process that mediated their feeling unsafe and keeping safe and resulted in being safe . Young Māori women's reflecting and learning facilitates relatively mature levels of resourcefulness for navigating being safe, including situations they encountered appear unsafe.